Early Christianity on the lower Maeander: between Ignatius and Apollo : Greek cities in the interplay of religious authorities - Huttner, Ulrich (Ancient Judaism and early Christianity, 2025)
"In Early Christianity on the Lower Maeander, Ulrich Huttner explores the religious authorities crucial for the poleis in the region (Miletus, Magnesia, Tralles, Nysa) and for shaping the conditions under which the Christian communities developed from the first to the fifth centuries. The Christians had to find their way between traditional institutions like the Oracle of Didyma and new impulses like those in the letters written by Ignatius of Antioch. While they were first still victims of local and imperial persecutions, from the 4th century onwards they enjoyed their superiority by demolishing pagan monuments"-- Provided by publisher